Social media on business strategies and impact on firm performance - Johari, Jalila; Viveganantha, Vikneaswari (Academic inspired network, 2022)
Social networking sites are essential for maintaining a competitive edge and those firms that have active social media may gain numerous marketing opportunities. The impact of using social media platforms among businesses has initiated new ways to strategize and increased firm performance among the listed companies. Thus, the main purpose of this study is to identify what type of information is disclosed on social media by publicly listed companies. The sample data was collected from 112 listed companies in Bursa Malaysia, which have social media accounts and are active in social media. Based on the descriptive result the companies are pertinent to disclose information on branding or product information, update the promotion, disclosure corporate social responsibility (CSR) activities carried out, and the organizational business activities in social media. The result also shows that there is a significant positive relationship between the usage of social media and the firm's performance. Although customers more react to promotion information disclosure as compared to other information disclosure, the companies actively disclose certain information on social media which may give impact the firm performance.